2007
DOI: 10.1158/1055-9965.epi-07-0413
|View full text |Cite
|
Sign up to set email alerts
|

Six-Month Follow-up of Patient-Rated Outcomes in a Randomized Controlled Trial of Exercise Training during Breast Cancer Chemotherapy

Abstract: Background: Few exercise trials in cancer patients have reported longer-term follow-up. Here, we report a 6-month follow-up of exercise behavior and patient-rated outcomes from an exercise trial in breast cancer patients. Methods: Breast cancer patients initiating adjuvant chemotherapy (n = 242) were randomly assigned to usual care (n = 82), resistance exercise training (RET; n = 82), or aerobic exercise training (AET; n = 78) for the duration of their chemotherapy. At 6-month follow-up, participants were mail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
120
2
10

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(136 citation statements)
references
References 25 publications
(35 reference statements)
4
120
2
10
Order By: Relevance
“…The intervention 287 also provides further support for the benefits of physical activity for self-esteem in breast cancer 288 patients [18]. Positive effects on self-esteem for an intervention that is implemented during 289 chemotherapy is particularly interesting, as treatment for breast cancer can result in negative effects 290 on body image and perceived femininity [44].…”
Section: Discussion 265mentioning
confidence: 94%
See 1 more Smart Citation
“…The intervention 287 also provides further support for the benefits of physical activity for self-esteem in breast cancer 288 patients [18]. Positive effects on self-esteem for an intervention that is implemented during 289 chemotherapy is particularly interesting, as treatment for breast cancer can result in negative effects 290 on body image and perceived femininity [44].…”
Section: Discussion 265mentioning
confidence: 94%
“…Physical activity interventions have varied in duration from 4 weeks [24] to 6 months [25] and have 76 been delivered in both individual [18] and group settings [13]. However, interventions that are 77 delivered in group settings, or that are hospital-based and/or supervised, can restrict participation as 78 patients undergoing chemotherapy are often busy with treatment schedules, are unwell or have limited 79 access to exercise facilities due to transportation or scheduling difficulties [16].…”
mentioning
confidence: 99%
“…One study suggested women who were previously inactive and increased their PA after breast cancer diagnosis had a 45% lower risk of death compared with women who remained inactive after diagnosis (7). Moreover, engaging in PA during adjuvant chemotherapy may aid in facilitating the adoption of PA after treatment (8).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Despite this knowledge, a little less than half the patients with CRF do not exercise due to physical, cognitive, and social reasons. 11,12 National clinical practice guidelines for managing cancer related fatigue recommend that healthcare professionals educate and provide exercise counseling by to patients who are in active treatment.…”
Section: 5mentioning
confidence: 99%